Diagnostic dilemmas and pitfalls in ThinPrep® cytology of breast fine needle aspiration biopsy: Report of Six Cases with Histological Correlates. Issue 7 (20th March 2017) - Scarpa Carniello, Jose Victor; Pareja, Fresia; Santos‐Zabala, Maria Laureana; Edelweiss, Marcia
Abstract : Fine needle aspirations (FNA) of the breast for primary diagnoses have become less popular in the USA and are usually performed for lesions with low or extremely high clinical suspicion. They are also performed for lesions in close proximity to a breast implant. Liquid‐based cytological preparations, such as ThinPrep ® (TP), provide a practical alternative to clinicians who are performing FNA. Using a selection of cases that represent challenging diagnoses, we describe common diagnostic pitfalls of breast FNA that are specifically associated with this preparation. Well known breast cytology pitfalls, such as fibroadenoma, when solely examined using a TP slide can be even more challenging since the usual stripped bipolar cells seen in the background of smeared slides, can appear singly dispersed with preserved cytoplasm, resembling carcinoma. We describe that large fragments of solid papillary carcinoma are represented by mostly singly dispersed cells with plasmacytoid features that mimic those of a lobular carcinoma. Since nuclear features are more pronounced in TP, prominent nucleoli and cytological atypia can potentially be overcalled. TP processing might also lead to clumping of epithelioid histiocytes that appear atypical, which increases the suspicion of malignancy. The presence of atypical cells in a TP slide of a peri implant seroma should always undergo additional testing, especially in patients with a prior history of breast carcinoma, to determine if it represents recurrent carcinoma or an implant associated anaplastic large cell lymphoma. Familiarity with the aforementioned artifacts associated with TP is essential to avoid diagnostic misinterpretations. Diagn. Cytopathol. 2017;45:655–661. © 2017 Wiley Periodicals, Inc.